Onkogeno delovanje herpesvirusov - Klemenc, Polona (Medicinski razgledi, 2003)
The first human tumour virus, virus Epstein-Barr, was discovered in 1964 in Burkitt's lymphoma cells. Oncogenic viruses are important for two main reasons. Firstly, approximately 15% of human cancer incidence can be attributed to a viral infection. Secondly, oncogenic viruses are analogous to other mutagenic carcinogens, being capable of initiating a chain of two or more events possibly leading to malignancy. Today it is known that many retroviruses produce tumours in domestic animals, and one has been implicated as a cause of human leukemia. The hepatitis B virus, flaviviruses, herpes viruses, especially the Epstein-Barr virus and herpes simplex virus 2, and several papillomaviruses are also implicated in cancer in humans. The greatestprospect for significantly reducing the frequency of cancer in humans is through immunisation against infection with oncogenic viruses.
Keywords: Herpesviridne infekcije; Oncogenic Viruses; Herpesviridae Infections; Herpesvirus 4 človeški; Onkogeni virusi; Tumor Virus Infections; Tumorski virusi, infekcije; Herpesvirus 4, Human; Apoptoza; Burkitt'S Lymphoma; Celica, transformacija virusna; Lymphoproliferative Disorders; Citokini; Lymphoma, T-Cell; Citomegalovirus; Nasopharyngeal Neoplasms; Herpesvirus 2 človeški; Herpesvirus 2, Human; Herpesvirus 6 človeški; Cell Transformation, Viral; Cytomegalovirus; Herpesvirus 7 človeški; Limfom T-celični; Herpesvirus 6, Human; Limfoproliferativne motnje; Herpesvirus 7, Human; Nazofaringealne novotvorbe; Sarcoma, Kaposi'S; virus; virusi; Cytokines; herpes virusi; Apoptosis; tumor; neoplasm; rak (medicina); biokemija